2010
DOI: 10.4166/kjg.2010.56.3.201
|View full text |Cite
|
Sign up to set email alerts
|

Remission of Ulcerative Colitis after Appendectomy: A Case Report

Abstract: The inverse correlation of appendectomy and ulcerative colitis is well known, but the effect of appendectomy on the clinical course of ulcerative colitis remains unclear. Although the majority of opinions were negative for the therapeutic advantage of appendectomy in patients with ulcerative colitis, advocates for positive effect of appendectomy have been proposed in a few case reports and a prospective study from Western countries. We herein report a case of ulcerative colitis who experienced clinical remissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…28-303339 There have been several case reports 3339 including one by Okazaki et al describing a case of mild UC proctitis “cured” by appendectomy after 3 years of follow up. 33 The largest case series by Bolin et al .…”
Section: Discussionmentioning
confidence: 99%
“…28-303339 There have been several case reports 3339 including one by Okazaki et al describing a case of mild UC proctitis “cured” by appendectomy after 3 years of follow up. 33 The largest case series by Bolin et al .…”
Section: Discussionmentioning
confidence: 99%
“…A study of IBD patients in Australia confirmed that appendectomy before diagnosis delays disease onset of both UC and CD and results in fewer flare-ups in the case of UC when compared with patients without prior appendectomy [107]. A case report from Korea also confirmed that a patient with UC experienced a more extended period of remission after appendectomy [108]. However, the therapeutic relationship between CD and appendectomy remains inconclusive.…”
Section: Appendectomymentioning
confidence: 97%